The Strategy for Maintaining the Marriage Household with Long-Distance Relationship of State Civil Apparatus at the Regional Office of the Ministry of Religious Affairs of Gorontalo Province - Titin Samsudin; Siti Anjarwati (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2021)
Long-distance marriage is a phenomenon that usually occurs for reasons such as work reasons. This study aims to examine the long-distance marriage of State Civil Apparatus (ASN) at the Regional Office of the Ministry of Religious Affairs of Gorontalo Province. This research is field research that presents a narrative, descriptive description of the informants with a normative, juridical and sociological theological approach. This study used primary data sources and secondary data. Data was collected through observation, in-depth interview, and documentation for further analysis. The research findings show that the long-distance marriage between Civil Servants in the Regional Office of the Ministry of Religious Affairs of Gorontalo Province is maintained with several strategies, including; good communication, open attitude, honesty, trust, setting the intensity of meetings, fulfilling a living (outwardly and spiritually), being responsible, finding solutions to every problem faced and strengthening and understanding religious values. The implication of the finding is that it can be a reference or reference for people who are undergoing long-distance marriage as a solution in maintaining the integrity of the household.